Implementasi Undang-Undang Keselamatan dan Kesehatan Kerja (Lex Jurnalica, 2009)
There are many Indonesia citizen in particular resident at silvan one is opting work as Labour Of Indonesia beyond seas, as at Saudi's Malaysia and Arab, to weigh working as farmer. If don't chance to abroad go to, therefore village resident is opting become labour at metropolises to weigh as farmer. Base Indonesian state constitution, section 27 sentence 2 UUD â€™ 45, every citizen really is entitled to work and subsistence that reasonably divides humanitarianism. But of course that citizen can carry on its work with every consideration, therefore needs to be given by protection by state. About problem which will be worked through deep observational it is hit, â€œWhat and How forms protection of state to its citizen in ketenagakerjaan's area?â€ In arrange this research writer uses to methodic normatif's law research.Â  One that intended with normatif's jurisdictional research is observational jurisdictional bibliographical. With descriptive character because gets form to enlighten or figuring an about problem by use of theories as base as to solve problems. Order hit safety And job health be meant to give protections for employ or labour of instance or adverse labor situation or gets to disadvantage health in order to that someone does work. Order hits safety and health job not know word as â€œ ought to â€, â€œbetter â€, â€œobviously â€. On the contrary, order about safety and job health constitutes â€œ instruction â€ or â€œ prohibition â€. Employer that doesn't ac-complish to command or employer that ignore its sanction prohibition be been threatened by criminal coop or fine.Â  Keywords: Implementation, Health,Â  Working Safety Law